Substantial contribution of tree canopy nitrifiers to nitrogen fluxes in European forests - Guerrieri, Rossella; Cáliz, Joan; Mattana, Stefania; Barceló, Anna; Candela, Marco; Elustondo, David; Fortmann, Heike; Hellsten, Sofie; Koenig, Nils; Lindroos, Antti-Jussi; Matteucci, Giorgio; Merilä, Päivi; et al. (Springer Nature, 2024)
Human activities have greatly increased the reactive nitrogen in the biosphere, thus profoundly altering global nitrogen cycling. The large increase in nitrogen deposition over the past few decades has led to eutrophication in natural ecosystems, with negative effects on forest health and biodiversity. Recent studies, however, have reported oligotrophication in forest ecosystems, constraining their capacity as carbon sinks. Here we demonstrate the widespread biological transformation of atmospheric reactive nitrogen in the canopies of European forests by combining nitrogen deposition quantification with measurements of the stable isotopes in nitrate and molecular analyses across ten forests through August–October 2016. We estimate that up to 80% of the nitrate reaching the soil via throughfall was derived from canopy nitrification, equivalent to a flux of up to 5.76 kg N ha−1 yr−1. We also document the presence of autotrophic nitrifiers on foliar surfaces throughout European forests. Canopy nitrification thus consumes deposited ammonium and increases nitrate inputs to the soil. The results of this study highlight widespread canopy nitrification in European forests and its important contribution to forest nitrogen cycling.